T Cell Activation and Regulation of HIV-1: Same Effectors with Distinct Outcomes - Jean-François Fortin; Benoit Barbeau; Gilles A Robichaud; Michel J Tremblay (Canadian Journal of Infectious Diseases)
The molecular mechanisms that regulate the function of the immune system and human immunodeficiency virus type-1 (HIV-1) gene expression are diverse and complicated. However, replication of HIV-1 is controlled by many of the same regulatory signals that play a crucial role in the transcriptional regulation of the immune system. For example, the viral promoter, as is the case for the immune system, is subject to complex regulation by combinations of cellular transcription factors that may quantitatively and/or qualitatively differ depending on cell types (eg, macrophages versus T lymphocytes) and cell states (eg, undifferentiated versus differentiated or quiescent versus activated). The present review discusses the regulation of HIV-1 gene expression by nuclear factor-kappa Band nuclear factor of activated T cells, and proposes that selective interference of these two cellular transcription factors may be a route to abrogate virus replication without disrupting normal cellular functions. A better understanding of the regulation of HIV-1 gene expression is of utmost importance for the design of molecular approaches that will effectively abrogate virus replication and, ultimately, disease progression.